Impact of Energy Poverty on Economic Development in Asia: An Empirical Analysis - Bui, Duy Hung; Do, Minh Thu (International Journal of Energy Economics and Policy, 2025)
This study provides an empirical analysis of the relationship between energy poverty and economic development across Asia from 2000 to 2022. Utilizing a panel dataset of 23 Asian economies, we employ access to electricity as a percentage of the population, access to clean fuels and technologies for cooking as a percentage of the population, and non-renewable final energy consumption per urban capita as proxies for foundational access, household human development, and the energy intensity of economic production, respectively. Through a suite of econometric techniques, including two-way fixed effects, instrumental variable (IV-2SLS), system Generalized Method of Moments (System GMM), and Panel Autoregressive Distributed Lag (ARDL) models, we uncover nuanced and policy-relevant dynamics. Our findings reveal that while all three dimensions of energy access are significantly and positively correlated with economic development, their magnitudes, transmission mechanisms, and policy implications differ profoundly. Specifically, the analysis highlights a critical divergence between the rapid expansion of electricity access and the persistently slow progress in clean cooking adoption, with the latter imposing substantial, often unseen, costs on health, and human capital formation.